Potential Interactions of Hypertension Drug in Medan City Pharmacy - Wahyuni, Sri; Rawitri, Kiki; Rahayu, Yayuk Putri (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Hypertension is a disease that can cause complications without the patient realizing it. Therapeutic management needed to control the patient's blood pressure is complex enough to potentially lead to drug interactions. The purpose of this study was to analyze the interaction of hypertension drugs that occurred in a pharmacy in the city of Medan. Method: The study was conducted retrospectively involving 101 patient data in February-May 2022. Patient data was processed descriptively and potential drug interactions were analyzed using the Medscape Drug Interactions Checker, Stockley's Drug Interaction, and the drugs.com database Result: Based on the study results, it was found that from 101 patients, 57 patients had no drug interactions (56.4%), but 45 cases of drug interactions were found in 44 patients (43.6%). Drug interactions found in 27 cases occurred pharmacokinetically (60%) and 18 cases occurred pharmacodynamically (40%). The most frequent drug interactions are Amlodipine and Simvastatin. Conclusion: Based on this study, it can be concluded that most patients who have drug interactions occur through pharmacokinetic mechanisms.